2015
DOI: 10.5194/hess-19-4619-2015
|View full text |Cite
|
Sign up to set email alerts
|

From runoff to rainfall: inverse rainfall–runoff modelling in a high temporal resolution

Abstract: Abstract. Rainfall exhibits a large spatio-temporal variability, especially in complex alpine terrain. Additionally, the density of the monitoring network in mountainous regions is low and measurements are subjected to major errors, which lead to significant uncertainties in areal rainfall estimates. In contrast, the most reliable hydrological information available refers to runoff, which in the presented work is used as input for an inverted HBV-type rainfall-runoff model that is embedded in a root finding al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…In recent years, for estimating and correcting rainfall, similar studies were published in which the secondary variable included land surface temperature [Wanders et al, 2015], Ku-band backscattering coefficient [Turk et al, 2015], microwave surface emissivities [Birman et al, 2015], and discharge [Kirchner, 2009;Herrnegger et al, 2015]. Similarly, Tian et al [2014] considered snow water equivalent observations for estimating snowfall at high latitudes.…”
Section: Indirect Validationmentioning
confidence: 99%
“…In recent years, for estimating and correcting rainfall, similar studies were published in which the secondary variable included land surface temperature [Wanders et al, 2015], Ku-band backscattering coefficient [Turk et al, 2015], microwave surface emissivities [Birman et al, 2015], and discharge [Kirchner, 2009;Herrnegger et al, 2015]. Similarly, Tian et al [2014] considered snow water equivalent observations for estimating snowfall at high latitudes.…”
Section: Indirect Validationmentioning
confidence: 99%
“…Die hydrologischen Modellierungen werden mit dem konzeptionellen, kontinuierlichen Niederschlags-Abfluss-Modell COSERO (COntinuous SEmidistributed RunOff Model) -Abb. 5; Nachtnebel et al 1993;Eder et al 2005;Herrnegger et al 2018Herrnegger et al , 2015aHerrnegger et al , 2015bHerrnegger et al , 2012Kling und Nachtnebel 2009;Kling et al 2015;Stanzel et al 2008 durchgeführt, welches auf dem HBV-Modell nach Bergström (1995)…”
Section: N-a-modellierungunclassified
“…The analysis of the error propagation in rainfall-runoff models, revealed that the precipitation errors tend to influence the results for long periods of time, and this influence largely depends on the conditions of the catchment when these errors occurred. Consequently, we advocate that methods where precipitation is estimated using inverse rainfall-runoff type model (Herrnegger et al 2015) under the assumption of a Markovian Process, have fundamental problems. The reason is in the explicit use of exact representation of the model states, which in practice is not possible for conceptual models, as processes are lumped at scales that do not match, and therefore, not measurable.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is required to establish a way to map from the model error into the inputs (inverse model), and therefore to the position of the DSN. Applications of inverse models to establish precipitation estimates from discharge have been proposed (Herrnegger et al 2015, Volkmann 2011, Kunstmann et al 2006).…”
Section: Can Model-based Objective Functions Be Used For Model-based mentioning
confidence: 99%
See 1 more Smart Citation